2021
DOI: 10.3892/mco.2021.2415
|View full text |Cite
|
Sign up to set email alerts
|

Urine TERT promoter mutations‑based tumor DNA detection in patients with bladder cancer: A pilot study

Abstract: Telomerase reverse transcriptase (TERT) promoter mutations are the most frequent genetic events in bladder cancer (BC). The aim of the present pilot study was to evaluate the diagnostic potential of urine TERT promoter mutations-based liquid biopsy in patients with an ongoing oncological process, as well as in post-resection patients at risk of BC recurrence. A total of 60 patients were enrolled, of whom 27 patients had histologically proven BC; 23 had no signs of BC (control group); and 10 patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…In a pilot study [ 49 ] TERT promoter mutations in urine were detected by Droplet Digital PCR. Diagnostic accuracy was evaluated in patients with ongoing oncology and after resection at risk of BCa recurrence.…”
Section: What Is New In the Last Two Years?mentioning
confidence: 99%
“…In a pilot study [ 49 ] TERT promoter mutations in urine were detected by Droplet Digital PCR. Diagnostic accuracy was evaluated in patients with ongoing oncology and after resection at risk of BCa recurrence.…”
Section: What Is New In the Last Two Years?mentioning
confidence: 99%
“…Such differences in the study populations yield significant differences in a marker’s reported efficacy parameters (i.e., sensitivity, specificity, positive and negative predictive values) of a marker in different studies ( Table 1 ). Therefore, unless a meta-analysis accounts/controls for the different variables across the studies, the reported mean and median efficacies would not be reliable, affecting a marker’s clinical translation [ 200 , 251 , 264 ].…”
Section: Clinical Translation Of Urine Biomarkers: Where Are We?mentioning
confidence: 99%
“…To counter some of the biases and inaccuracies associated with biomarker studies, the STARD (Standards for Reporting of Diagnostic Accuracy Studies), PRISMA (The Preferred Reporting Items for Systematic reviews and Meta-Analyses), and the updated PRISM-DAT (PRISMA-Diagnostic Accuracy Test) statements/guidelines could be adopted in the meta-analyses and systematic reviews of BC biomarkers [ 264 , 265 , 266 , 267 , 268 ]. Nevertheless, very few biomarker studies for malignant or benign diseases adhere to these guidelines.…”
Section: Clinical Translation Of Urine Biomarkers: Where Are We?mentioning
confidence: 99%
“…Bladder cancer (BC) is considered the most common urinary tract malignancy, ranking 9 th and 13 th in terms of frequency mortality rates respectively [1]. BC occurrences and mortalities are generally associated in regions with high human development index [2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to both recent advances in genomic, epigenomic and proteomic studies of tumor fluids, and the development of sensitive analytical molecular techniques, a new approach for cancer detection has emerged, namely liquid biopsy. This technique is based on the analysis of various tumor-related targets circulating in biological fluids, such as blood, urine, saliva and cerebrospinal fluid [1]. These targets include cell-free tumor DNA (tDNA), different types of tumor RNAs, peptides, metabolites, exosomes, endosomes, and even circulating tumor cells [8].…”
Section: Introductionmentioning
confidence: 99%